Bonhoeffer's Christocentric Theology and Fundamental Debates in Environmental Ethics - van den Heuvel, Steven C. (Eugene : Wipf and Stock Publishers, 2017)
There is widespread understanding of the close connection between religion and the ecological crisis, and that in order to amend this crisis, theological resources are needed. This monograph seeks to contribute to this endeavor by engaging the theology of Dietrich Bonhoeffer. His theology is particularly suitable in this context, due to its open-ended nature, and to the prophetic and radical nature of the questions he was prepared to ask--that is why there are many other attempts to contextualize Bonhoeffer's theology in areas that he himself has not directly written about. In this monograph
Description based upon print version of record.
Includes bibliographical references (pages 275-300) and indexes.
Master record variable field(s) change: 050, 072, 082 - OCLC control number change
Keywords: Bonhoeffer, Dietrich, -- 1906-1945.; Bonhoeffer, Dietrich, -- 1906-1945 -- Ethics; Jesus Christ -- Person and offices; Bonhoeffer, Dietrich, -- 1906-1945.; Jesus Christ; Ecology -- Religious aspects -- Christianity; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Christology; Ecology -- Religious aspects -- Christianity; Ethics; Electronic books; Electronic books